IMPLEMENTASI METODE CARD SORT PADA PEMBELAJARAN FIQIH DI MAN 3 PASAMAN BARAT - Odik Fraydika (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
Implementation of Card Short Method on Fiqh Learning in MAN 3 West Pasaman, In the process of learning Fiqh teachers use card sort method. At the beginning of the learning activities teachers form several teams. Give each team a set of shuffled cards so that the categories they sort are invisible. the teacher asks each team to sort the cards into specific categories. Each team gets a score for each card that is sorted correctly. Here the type of research that researchers use is field research (field reseacrh) that is descriptive by using qualitative analysis. Descriptive methods can be interpreted as problem solving procedures investigated by describing research objects based on visible facts or as they are. With data collection techniques, namely observation and interview. Regarding the process of learning fiqh in Man 3 West Pasaman the author sees that teachers who teach fiqh subjects have used the card shot method to convey the learning materials that will be delivered, so that the learning in the classroom runs smoothly with the time that has been determined. A learning in order to achieve its objectives must be implemented in accordance with the procedures and rules that apply, using the card shot method. So that the learning process can run well and the learning materials can be achieved in accordance with the planned objectives. However, this MAN 3 West Pasaman school, if the teacher always uses the card shot method in learning students will become lazy to learn, because students are asked to think with the time that has been determined and students are told to contemplate one by one in the future, thus making students lazy to do so. It is recommended that teachers also use the lecture method before doing this card shot method or by giving quis after the percentage done by the student